If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14a + 12b + 5c + 4c + -6b + -4a = 0 Reorder the terms: 14a + -4a + 12b + -6b + 5c + 4c = 0 Combine like terms: 14a + -4a = 10a 10a + 12b + -6b + 5c + 4c = 0 Combine like terms: 12b + -6b = 6b 10a + 6b + 5c + 4c = 0 Combine like terms: 5c + 4c = 9c 10a + 6b + 9c = 0 Solving 10a + 6b + 9c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. 10a + 6b + -6b + 9c = 0 + -6b Combine like terms: 6b + -6b = 0 10a + 0 + 9c = 0 + -6b 10a + 9c = 0 + -6b Remove the zero: 10a + 9c = -6b Add '-9c' to each side of the equation. 10a + 9c + -9c = -6b + -9c Combine like terms: 9c + -9c = 0 10a + 0 = -6b + -9c 10a = -6b + -9c Divide each side by '10'. a = -0.6b + -0.9c Simplifying a = -0.6b + -0.9c
| 6x-20=7x+7 | | 220-5p=-20+3p | | 15=-18(b-1)+9 | | 3x-4=12-31 | | 2p+3q=-5 | | (h+8)(h-2)(H)=96 | | (1-x*x*x)*(3x*x-5z)= | | 2.25a-7.5=21 | | 3(2x+4)=6(x+3) | | a=1500(1+0.067)27 | | -20=-11s+4 | | 8g-7+2g=13 | | 5x+1=2x-9 | | 3cos^2x=3-cos^2x | | 4x+1=15+2x | | 4y^2+34y=-144 | | -6x-28+8x=14 | | 20-2P=-10+4P | | [8+5y]=14 | | 3.5x+-20+.5x=40-2x | | -7=6-C | | 7x+5x-65=79 | | 9y=5x-7 | | 5x+8y+4xy= | | Y=24x+15 | | 4x+2=-25 | | 27-9x+15y=0 | | 4cosx+2=cosx+1 | | 6-9p-2= | | 3ln(x-2)+6=7 | | y+2-3y=-18 | | 5x+8=5(x+2) |